General assessment and development orientation for 50 coastal islands in Northern Vietnam (with an area of 1 km2 or more) - Khanh, Uong Dinh; An, Le Duc; Dung, Bui Quang (Vietnam Journal of Marine Science and Technology, 2019)
Vietnam has about 2,773 islands located in the coastal areas of different seas, including around 100 islands with an area of 1 km2 or more (these islands are large enough for socio-economic development). Northern coastal area has 50 islands with an area of 1 km2 or more, distributed in two provinces Quang Ninh (47 islands), Hai Phong (3 islands). According to a combined assessment of the potential and position of 50 Northern coastal islands for the purpose of economic development, defense and security, 9 islands have been recognized as having the capability of defense and economic development; 6 islands have the advantages of economic development and national defense; 16 islands have the primary function of economic development and 19 islands should focus on their advantages of tourism and agroforestry, which will also be considered as a reserved resource for future island economic development